The Effects of Brand Image on Customer Satisfaction and Loyalty Intention in Retail Super Market Chain UK - Neupane, Ramesh (International Journal of Social Sciences and Management, 2015)
The main purpose of this research is to examine the effects of brand image on customer satisfaction and loyalty intention. It also examines the relationships between the brand image and customer satisfaction, brand image and loyalty intention as well as customer satisfaction and loyalty intention on the context of retail supermarket chain in UK. The hypotheses were formed on the basis of existing literatures and data was collected to test the hypotheses so it is deductive research. The survey strategy is used to collect information from the customers of the main six retailers based on London through structured closed ended questionnaires at a point of time and so it is cross-sectional research. A sample of 120 customers was selected through convenience sampling technique. The statistical and mathematical tools such as percentage analysis, correlation and regression analysis are used for data analysis through SPSS 20. This study asserts that the overall brand image has significant effects (P = 0.000 and β = 0.880) on customer satisfaction. Similarly, the overall brand image has significant effects (p = 0.000 and β = 0.780) on overall customer loyalty intention; and also customer satisfaction has significant positive effects (p = 0.000 and β = 0.859) on customer loyalty intention in an organisation. However, this study considered just five variables of brand image and five variables of customer satisfaction. There may have other important factors which may influence the findings. A small sample size of just 120 customers from just six stores of the main retailers may not represent the vision of all retail customers. Thus, it is recommended that a large scale research with more variables, large sample size with more stores from different parts of the UK to validate these findings. DOI: http://dx.doi.org/10.3126/ijssm.v2i1.11814 Int. J. Soc. Sci. Manage. Vol-2, issue-1: 9-26